Microstructural studies of strontium titanate ceramic pressed at varying pressure - Mat Syned, Nadiah (2014)
The purpose of this study is to fabricate the Strontium Titanate (SrTiO3) ceramics by using the High Energy Ball Milling Method (HEBM) for 9 hours at varying pressure between 60 MPa to 160 MPa at an interval 20 MPa. The samples were sintered at 1100 °C. The microstructures and morphology the samples were investigated by X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) respectively. Meanwhile, the densities and porosities of the ceramics were determined via Archimedes’ method. The smallest crystallite size, 40.8 nm at 140 MPa and particle size, 0.58 ?m were found at the pressure 160 MPa this is due to the decreased of large voids by reorganization of granules. The maximum density of the samples was found to be 4.99 gcm-3 at 140 MPa while the porosity was 22.35 % at 60 MPa.